UPAYA MENINGKATKAN HASIL BELAJAR KETERAMPILAN MENGGIRING BOLA MELALUI MEDIA PEMBELAJARAN BOLA PLASTIK DI SEKOLAH DASAR - Syamsudin, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problems discussed in this research is how to improve learning activities dribble with plastic balls on the fifth grade students of SDN 26 Nanga Pinoh Melawi. The purpose of this study was to determine the learning outcome dribbling skills with a plastic ball on the class V students of SDN 26 Nanga Pinoh Melawi. This research uses research "Classroom Action Research" (Classroom Action Research) with variables: Increased dribble with plastic balls. Subjects in this study were fifth grade students of State Elementary School 26 Nanga Pinoh Melawi totaling 28 students, This research technique using test and measurement, a test with a grating instrument measuring learning outcomes dribbling skills. Analysis of data using percentages. These results indicate there is an increase in learning activities dribble with plastic balls on the fifth grade students of SDN 26 Nanga Pinoh Melawi. This is evidenced by the increased skills lead the game of football is pretty good, that in the first cycle with an average value of 74.31 so the increase of 8.45%. while the average value on the second cycle is 83.10, so the increase of 21.28%.Â Keywords: Modification, instructional media, learning outcomes, dribble.Â Â